Effects of Hyperoxia and Mild Therapeutic Hypothermia During Resuscitation From Porcine Hemorrhagic Shock*. Issue 5 (May 2016) - Knöller, Elisabeth; Stenzel, Tatjana; Broeskamp, Friederike; Hornung, Rouven; Scheuerle, Angelika; McCook, Oscar; Wachter, Ulrich; Vogt, Josef A.; Matallo, José; Wepler, Martin; Gässler, Holger; Gröger, Michael; et al.
Abstract : Objective: Hemorrhagic shock–induced tissue hypoxia induces hyperinflammation, ultimately causing multiple organ failure. Hyperoxia and hypothermia can attenuate tissue hypoxia due to increased oxygen supply and decreased demand, respectively. Therefore, we tested the hypothesis whether mild therapeutic hypothermia and hyperoxia would attenuate postshock hyperinflammation and thereby organ dysfunction. Design: Prospective, controlled, randomized study. Setting: University animal research laboratory. Subjects: Thirty-six Bretoncelles-Meishan-Willebrand pigs of either gender. Interventions: After 4 hours of hemorrhagic shock (removal of 30% of the blood volume, subsequent titration of mean arterial pressure at 35 mm Hg), anesthetized and instrumented pigs were randomly assigned to "control" (standard resuscitation: retransfusion of shed blood, fluid resuscitation, norepinephrine titrated to maintain mean arterial pressure at preshock values, mechanical ventilation titrated to maintain arterial oxygen saturation > 90%), "hyperoxia" (standard resuscitation, but FIO2, 1.0), "hypothermia" (standard resuscitation, but core temperature 34°C), or "combi" (hyperoxia plus hypothermia) ( n = 9 each). Measurements and Main Results: Before, immediately at the end of and 12 and 22 hours after hemorrhagic shock, we measured hemodynamics, blood gases, acid-base status, metabolism, organ function, cytokine production, and coagulation. Postmortem kidney specimen were taken for histological evaluation, immunohistochemistry (nitrotyrosine, cystathionine γ-lyase, activated caspase-3, and extravascular albumin), and immunoblotting (nuclear factor-κB, hypoxia-inducible factor-1α, heme oxygenase-1, inducible nitric oxide synthase, B-cell lymphoma-extra large, and protein expression of the endogenous nuclear factor-κB inhibitor). Although hyperoxia alone attenuated the postshock hyperinflammation and thereby tended to improve visceral organ function, hypothermia and combi treatment had no beneficial effect. Conclusions: During resuscitation from near-lethal hemorrhagic shock, hyperoxia attenuated hyperinflammation, and thereby showed a favorable trend toward improved organ function. The lacking efficacy of hypothermia was most likely due to more pronounced barrier dysfunction with vascular leakage–induced circulatory failure. Abstract : Supplemental Digital Content is available in the text.